Color of cooked ground beef patties is affected by cooking rate and post-cooking holding time - Ryan, S.M.; Seyfert, M.; Hunt, Melvin C.; Mancini, R.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments investigated the effects of cooking rate and post-cooking holding time on the internal cooked color of ground beef patties. In Experiment 1, patties were cooked rapidly (1.8ºF/second) or slowly (0.4ºF/second). At temperatures below 180ºF, rapidly cooked patties were redder and appeared less well done than those cooked slowly. All slowly cooked patties appeared well done, even at unsafe final internal temperatures. In Experiment 2, patties were cooked rapidly and held for 1, 3, 6, or 12 minutes after cooking. Increasing the post-cooking holding time to 6 minutes after rapid cooking decreased pinkness and maximized well-done appearance. This allowed ground beef patties to be cooked to a lower temperature, likely preserving juiciness and flavor. Employing either a slow cooking rate or rapid cooking with a post-cooking holding time will foster a well-done appearance. Internal cooked color is not an adequate indicator of ground beef doneness. Only strict temperature control and monitoring can ensure product safety.
Keywords: Beef; Ground beef; Cooking rate; Post-cooking holding time